ANALISIS PENGARUH KUALITAS AUDIT, UKURAN PERUSAHAAN, LEVERAGE DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia - Alfia Nur Ubay (AKT 16 UMY 126, 2016)
Earnings management is the act of a manager to present a report to raise or lower the current period earnings of the business units under their responsibility, without causing an increase or decrease in the unit of economic profitability in the long term. This study aimed to examine the influence of auditors, company size, leverage and institutional ownership to earnings management. The sample used in this study consisted of a sample of 144 manufacturing companies listed in Indonesia Stock Exchange (IDX) during the 2011-2014 period. Samples were selected using purposive sampling method. Earnings management is a proxy with discretionary accruals using the Jones Model Modified (1995). Data collection method used is secondary data. Analysis of the data used in this study with descriptive statistical analysis, the classical assumption test, multiple linear regression analysis, determination analysis, t test and F test. The results showed that the quality of the audit and the leverage it has no influence on earnings management, the size of the company has a significant positive effect on earnings management, whereas institutional ownership has a significant negative effect on earnings management.